1995
DOI: 10.1083/jcb.130.5.1093
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in glyceraldehyde 3-phosphate dehydrogenase alters endocytosis in CHO cells.

Abstract: Abstract. The CHO cell mutant FD1.3.25 exhibits both increased accumulation and altered distribution of endocytosed fluid phase tracers. Neither the rate of tracer internalization nor the kinetics of recycling from early endosomes was affected, but exocytosis from late endocytic compartments appeared to be decreased in the mutant. Endocytosed tracer moved more rapidly to the cell poles in FD1.3.25 than in wild type cells. An abundant 36-kD polypeptide was found associated with taxol-polymerized microtubules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…The ubiquity of GAPDH has been the subject of several reports in the literature (Huitorel and Pantolini, 1985;Kawamoto and Caswell, 1986;Allen et al, 1987;Meyer-Siegler et al, 1991;Pancholi and Fischetti, 1992;Singh and Green, 1993;Robbins et al, 1995;GilNavarro et al, 1997) and the results presented in this paper clearly show that this GAPDH protein (p37) has other functions than its glycolytic enzymatic activity, as its oversynthesis in¯uences growth, biomass yield, cell wall stability, cell morphology and aggregation. There is now evidence that p37 can induce cell aggregation in Saccharomyces, although it is a Kluyveromyces protein.…”
Section: Discussionsupporting
confidence: 57%
“…The ubiquity of GAPDH has been the subject of several reports in the literature (Huitorel and Pantolini, 1985;Kawamoto and Caswell, 1986;Allen et al, 1987;Meyer-Siegler et al, 1991;Pancholi and Fischetti, 1992;Singh and Green, 1993;Robbins et al, 1995;GilNavarro et al, 1997) and the results presented in this paper clearly show that this GAPDH protein (p37) has other functions than its glycolytic enzymatic activity, as its oversynthesis in¯uences growth, biomass yield, cell wall stability, cell morphology and aggregation. There is now evidence that p37 can induce cell aggregation in Saccharomyces, although it is a Kluyveromyces protein.…”
Section: Discussionsupporting
confidence: 57%
“…We also detected low levels of Ca 2ϩ -independent aggregation and fusion activities, but this accounted for only a small fraction of that achievable with Ca 2ϩ (not shown). We have also shown that GAPDH in our fusion system apparently has a potential for Ca 2ϩ -mediated fusion that is at least equivalent to annexin I. Robbins et al [28] recently discovered in late endosomes that a single amino acid substitution in GAPDH caused a marked difference in endocytosis of liquid phase markers. Thus, it can be seen in an unrelated system that GAPDH appears to serve in a membrane-membrane fusion capacity.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, it is clear now that GAPDH displays a distinct membrane, cytosolic and nuclear localization. In those subcellular sites, it is involved in a number of cellular functions, including endocytosis and membrane fusion (Glaser and Gross, 1995;Robbins et al, 1995), vesicular secretory transport (Tisdale, 2001), translational control (Yi et al, 2000), nuclear tRNA transport (Singh and Green, 1993), DNA replication (Zheng et al, 2003) and DNA repair (Krynetski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%